Measure the quality of Islamic banking customer perspective, Empirical Study on some Islamic banks Arabia - عبد الله السبئي, صادق احمد (Journal of Economics and Administrative Sciences, 2017)
This study aims to identify the level of quality of  Islamic banking services in the Kingdom of Saudi Arabia. It also investigates the importance of  the various dimensions of the quality of banking services. The sample of the study included 69 clients of Al Rajhi Bank and  Al-Bilad Bank. The study concluded that the overall level quality of services that Islamic banking offer is high. However, their relative importance varies from one dimension to another. The security, confidence and physical aspects are very high which this is a good point. On the other hand, the application aspects do not get the same importance. These aspects include the customer's wishes, helping them to improve the services offered to them, and the personal attention of the customer. The most important dimension the Islamic banks have been established to